Biodegradable fishing gear: A sustainable solution to ghost net pollution in marine environments - Aslonov, Shahram; S.B, Gulamov; M. Hassan, Muntather; Chittipedhi, Krishna; Safarbaev, Otabek; Das Vaishnav, Venu Anand (International Journal of Aquatic Research and Environmental Studies, 2025)
The environmental repercussions of losing fishing gear in the ocean include conventional fishing equipment, which is primarily made of polyamide, a non-biodegradable material, resulting in long-lasting marine pollution, microplastic production, chemical pollution, and ghost fishing due to the material’s stubbornness. It is further suggested that co polyesters based on PBSAT and PBSA are more sustainable alternatives to the conventional materials because they do not pose issues like polybutylene succinate-co adipate-co-terephthalate or polybutylene succinate-co-butylene adipate. Progressing degradation processes give the sheer breadth of plastic waste a focus point, heterogeneous aging of polymer materials, biopolyesters such as marine litter, or the active research of potential recovery methods. This research investigates the hydrolytic aging of PBSAT and PBSA and compares them alongside PA monofilaments in pure water conditions. The materials were subjected to accelerated aging tests at four distinct temperatures: twenty five-degree intervals from forty to eighty degrees Celsius. Additionally, utilizing single factor modeling, a mechanical strength reduction framework was created based on differing end-of-life criteria around 2, 10, 15, 20, 30 degrees Celsius. Results indicate monofilaments with biosourced raw materials versus those fabricated from non biodegradable PA plastics are far more susceptible to hydrolysis in terms of mechanical strength. Furthermore, the volatile operational expectancy renders the gear irrelevant long before projected deterioration thresholds are theorized. As an example, PBSAT would have a 50% loss in tensile strength after roughly 10 years, PBSA would reach this mark after 20 years, and PA would reach this at 1000 years, all occurring at 2°C.